Clinical Case: Use of Rectal Ozone Therapy and Ozonized Saline Solution in Patient with Covid-19 Pneumonia (Ozone Therapy Global Journal, 2021)
COVID-19 is a life-threatening pandemic disease that has a huge social, economic and health impact. It usually manifests as an acute respiratory infection, although it can be asymptomatic. 40% of cases develop mild symptoms; 40%, moderate symptoms; 15% severe and 5% critical condition. It does not have specific effective treatment at present. There are studies that support the use of ozone as an antiviral, stimulator of cellular immunity, anti-inflammatory, antioxidant and stimulator of oxygenation in hypoxic tissues. These properties justify its use in this pathology. We present the case of a patient with moderate to severe COVID-19 pneumonia initially treated with rectal ozone insufflations that were ineffective in achieving clinical recovery. Subsequently, ozonized saline was administered, with which it was quickly possible to reverse the unfavorable evolution and achieve clinical recovery, from laboratory and imaging tests, without presenting any adverse reaction to treatment. It is concluded, based on clinical, laboratory and imaging data, that ozonized saline is an effective and safe form of systemic ozone therapy in the patient with moderate to severe COVID-19